Recent Advances in Thrombosis and Hemostasis 2008 - Tanaka, Kenzo (Springer, 2017)
Now more than ever, thrombotic and thromboembolic disorders as well as related diseases such as malignancies, arteriosclerosis, diabetes mellitus, hypertension, and obesity are the leading causes of morbidity and mortality. They have become urgent medical problems with serious economic consequences in industrialized and devel- ing countries alike. At the same time, the impact of molecular biology and genetics on our understanding of thrombosis and hemostasis is rapidly growing stronger as well as our knowledge of regeneration and development of specific tissues, organs, and embryos. Researchers are also constantly learning more about cardiovascular diseases as well as regulatory mechanisms for various intrinsic and extrinsic stimuli in viable tissues. In this volume, our intention has been to present the latest relevant information in molecular biology and genetics as well as the clinical implications of a better understanding of pathophysiology, novel diagnostic methodologies, and therapeutic applications for new methods of prevention in thrombosis/hemostasis and related disorders, including atherosclerosis. The dramatic advances in knowledge of thrombosis/hemostasis and vascular biology since the first publication of Recent Advances in Thrombosis and Fibrinolysis, edited with Japanese colleagues, in 1991, have required extensive revision in order to highlight and review recent progress in the field. The editors also gratefully welcome the seven distinguished non Japanese authors, who, with their valuable contributions on subjects beyond the coverage by Japanese authors, have made this new edition truly international.